Material de cama: Qualidade, quantidade e efeito sobre o desempenho de frangos de corte - De Angelo, João Carlos [UNESP]; Gonzales, Elisabeth; Kondo, Nancy [UNESP]; Anzai, Nelson Haruo [UNESP]; Cabral, Maurício Medeiros [UNESP] (My University, 1997)
An experiment was conducted to evaluate performance, mortality and incidence of lesions on the breasts, hocks and foot pads of broilers raised on wood-scrap litter, rice hulls, Brachiaria hay (Brachiaria decumbens), Napier hay (Pennisetum purpureum) and Coast-cross hay (Cynodon dactylon). A randomized experimental design with five litters, two sexes, four replications and fifty birds per box was used. A standard litter height of 5 cm of wood-scraps and a weight of 2025Og were adopted as criteria for use of other materials in the boxes.The amount of excreta deposited was 1697 g per raised bird (34,00 % of feed consumption). The incidence of lesions was evaluated in five birds per box after 35, 42 and 49 days and after slaughter. The criteria for scoring lesions were: 0 = without lesion; 1 = inflammation; 2 = mild ulceration; 3 = severe ulceration. At the end of experimental period (49 days) no differences were observed for weight, weight gain, feed consumption, feed/gain ratio and mortality among treatments. The lesions of the hocks and foot pads of the birds, raised on either Coast-cross hay and Napier hay, were more severe than those on wood-scraps and Brachiaria hay. Males showed better performance than females, but their hock lesions were more severe, independent of the litter used. Based on the performance and lesions scores, it was concluded that Braquiaria hay could be used as litter in replace wood-scraps and rice hulls.
Effect of quality and quantity of litter material on the performance of broilers
Keywords: Breast; Broiler; Foot pad; Hock; Lesions; Litter; Performance